Long-Term Implant Survivorship of Cementless Total Knee Arthroplasty: A Systematic Review of the Literature and Meta-Analysis - Mont, Michael A.; Pivec, Robert; Issa, Kimona; Kapadia, Bhaveen H.; Maheshwari, Aditya; Harwin, Steven F. (The Journal of Knee Surgery, 2014)
Cementless total knee arthroplasty (TKA) has had limited use in the United States, however, recent reports have demonstrated promising results, but there has been no meta-analysis to examine these outcomes in the past 5 years. In this review, 37 studies (2,940 patients and 3,568 TKAs) were identified and used, comparing cementless to cemented TKA. Pooled implant survivorship was compared using a fixed-effect meta-analysis between cementless and cemented TKA, and between cementless TKA with and without screw fixation. Cementless TKA had implant survivorship comparable to cemented TKA (odds ratio, 1.1; 95% confidence interval [CI], 0.62–2.00). The mean survivorship at 10 years for cementless TKA was 95.6% compared with 95.3% for cemented TKA. At 20-year follow-up, implant survivorship decreased to 76 and 71%, respectively. No difference was observed between fixation with or without screws (OR, 1.1; 95% CI, 0.16–7.5). Implant survivorship for cementless TKA was comparable to the current gold standard cemented TKAs.
Keywords: total knee arthroplasty; cementless